Anticolitic Effect of Berberine in Rat Experimental Model: Impact of PGE2/p38 MAPK Pathways - Li Jia; Kuijin Xue; Junheng Liu; Ola A. Habotta; Lianhai Hu; Ahmed E. Abdel Moneim (Hindawi Limited, 2020)
Berberine (BER), a natural isoquinoline alkaloid, has been demonstrated to have appreciable anticolitis effects. Nevertheless, the protective mechanism of BER in ulcerative colitis (UC) is barely understood. The present study was aimed at exploring the therapeutic efficacy of BER on UC in experimental colitis rat model. Rats were orally administered with BER for seven days at low and high doses (25 and 50 mg/kg/day) before AcOH intracolonic instillation. BER significantly retrieved colon inflammation and mucosal damage indicated by inhibition of macroscopic score and lessened the levels of inflammatory biomarkers (IL-1β, IL-6, TNF-α, MPO, and PGE2). Notable downregulation of mRNA expression of p38 MAPK and increased protein expression of TGF-β were achieved by BER treatment. The anti-inflammatory potential of BER was supported by the histopathological screening of colon mucosa. In addition, BER restored colonic antioxidant capacity through elevation of GSH level and antioxidant enzymatic activities (SOD, CAT, GPx, and GR) together with reductions of both MDA and NO levels. Marked downregulation of Nos2 mRNA expression is accompanied by increased Nrf2 and Hmox-1 expressions in colon specimens treated by BER. Furthermore, BER exhibited noticeable antiapoptotic activities through decreasing proapoptotic proteins (Bax and caspase-3) and lessening antiapoptotic Bcl-2 protein in the colon mucosa. Based on these findings, BER may improve colitis markedly which may be mediated by its striking antioxidant, anti-inflammatory, and antiapoptotic properties.